Proposta de um sistema computacional para análise entre a resposta em freqüência e o índice de reverberação para ambientes fechados de pequeno porte - Capelas, Maurício (2004)
This work shows the importance for acoustic treatment in small and closed rooms, to improve, not only the acoustic comfort, but also the system intelligibility. Formulas to calculate the reverberation time for small and closed rooms have been used, comparing each one in a graphic, showing their applicability. In the real case study, the reverberation time decreases has been compared with the sound pressure levei decreases, using a real time analyzer. With this information, a software has been developed, using Delphi skills. Delphi has a good user’s graphic interaction, is friendly user software, allowing a fast actualization and continuously increment. And in a future works, the sound sources positioning, furniture and peoples inside the room, will be implemented to improve the options for acoustic treatment.